Personal Values as a Proponent of Intention for Socially Responsible Investment - Prakoso, Bagas Adi; Putra, Tegar Satya (KINERJA, 2025)
Historically, investors have only viewed investments conventionally without looking at their behaviors. The intention formed by an individual will occur through attitude. As in the investment world, investors will intend to invest when there is a drive. The encouragement is formed through the values held by the investor. The evolution of the investment world makes investors not only see an investment conventionally, namely by looking at profit and loss, but also in terms of investors' financial behavior. Therefore, this study will explore the relationship between collectivism, materialism, and environmental attitude towards socially responsible investment (SRI). In addition, this study will also look at the relationship between attitude towards SRI and investor’s intention to invest in SRI. This research uses the PLS-SEM method with five latent variables mentioned earlier. The result of this study indicates a positive effect of attitude towards SRI on investment intention in SRI. In addition, environmental attitude shows a significant influence on attitude towards SRI. These findings suggest that companies can increase awareness of environmental issues to gain investor interest and build investor confidence to invest in the company.